2013
DOI: 10.3174/ajnr.a3488
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Whole-Brain White Matter by DTI in Autosomal Recessive Spastic Ataxia of Charlevoix-Saguenay

Abstract: BACKGROUND AND PURPOSE:Extension and characteristics of WM involvement other than the brain stem remain inadequately investigated in ARSACS. The aim of this study was to investigate whole-brain WM alterations in patients with ARSACS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 37 publications
1
9
1
Order By: Relevance
“…To the best of our knowledge, Turkish patients with ARSACS have been previously reported. [ 6 7 8 ] Detected mutations in previously reported Turkish patients were different from that of our patient. We identified the same mutation that was reported in a study by Synofzik et al .…”
Section: Discussioncontrasting
confidence: 85%
“…To the best of our knowledge, Turkish patients with ARSACS have been previously reported. [ 6 7 8 ] Detected mutations in previously reported Turkish patients were different from that of our patient. We identified the same mutation that was reported in a study by Synofzik et al .…”
Section: Discussioncontrasting
confidence: 85%
“…This limitation is increasingly important to emphasize as specific pathologic white matter changes are now commonly implied in human studies based solely upon directional diffusion metrics in the absence of ground truth pathologic validation. [34][35][36][37][38][39][40] Although EB demyelination has been extensively utilized to study mechanisms of endogenous and graft-mediated remyelination, 23,[41][42][43] to our knowledge this is the first study to examine MRI features of EB-induced injury. EB demyelination does not precisely replicate Color image is available online at www.liebertpub.com/neu any known clinical disease; however, it is ideally suited for evaluating diffusion MRI correlates of myelin pathology in vivo in the absence of significant secondary axonal injury or primary inflammatory response.…”
mentioning
confidence: 99%
“…The first mutations were observed in 2004: this study reported two missense (W1196R and N3799D) mutations and two indels (L3193-fsX3199 and T2683-fsX2708)[ 55 , 56 ]. Later, additional mutations were also discovered: Oguz et al analyzed nine unrelated families and revealed eight novel mutations in the SACS gene (5019A>G/F4011S, 14370G>T/S894X, 12841T>A/K1404X, 5031 G>A/ S4007F, 12660A>G/ I1464T, 8346–8347insT, 5677G>A/ R3801, 5566delC), and one variant (6945A>G/V3369A) [ 57 ]. Kurt et al reported a homozygous G2772A mutation in a Turkish female patient with ataxia and spondyloepiphyseal dysplasia, but it was heterozygous in unaffected family members.…”
Section: Sacs Genetics and Mutationsmentioning
confidence: 99%